Pengelolaan Keuangan Keluarga di Masa Pandemi Covid-19 - Halpiah Halpiah; Hery Astika Putra; Baiq Rizka Milania Ulfah (Indonesian Journal Publisher, 2021)
Problems that often arise in the family/ household are quite complex. One of them is economic problems or financial problems, especially during the Covid-19 pandemic requiring careful financial management by making a priority scale where prioritizing expenditures based on needs compared to spending based on desires in order to avoid debt and receivables. The method in implementing PKM is carried out in three stages, namely 1) The preparation stage includes community situation analysis, identification of problems, determining PKM work objectives, determining the theme and schedule for PKM implementation, division of PKM tasks, 2) Implementation stage including presentation of material delivery with the lecture method, question and answer session, mentoring session for making financial management to participants, 3) Evaluation stage. This PKM activity was carried out by implementing the Covid-19 Health protocol which was attended by 20 participants, which were dominated by women who were married or had families. The goal is that these housewives are able to record every income and are able to track daily expenses that have been issued in one month by way of prioritizing financial management. The conclusion from this PKM was that the 20 participants who attended had never done financial management, not because they were unable or unwilling but there had never been any socialization about financial management and the lack of basic knowledge about financial management so that economic problems in finance were always repeated. Therefore, PKM activities regarding financial management are still very important to be carried out with the main target being women / housewives as literacy efforts in financial management so that they are able to distinguish between productive expenditures and consumptive expenditures as financial managers in the family.